Rituximab Immunomonitoring Predicts Remission in Membranous Nephropathy - Teisseyre, Maxime; Cremoni, Marion; Boyer-Suavet, Sonia; Crepin, Thomas; Benzaken, Sylvia; Zorzi, Kévin; Esnault, Vincent; Brglez, Vesna; Seitz-Polski, Barbara (Frontiers in Immunology, 2021)
Primary membranous nephropathy (pMN) is an autoimmune kidney disease and a common cause of nephrotic syndrome in adults. Rituximab is becoming a first line therapy for patients with persistent nephrotic syndrome with proven safety and efficacy, achieving remission in 60%–80% of cases. For the remaining 20%–40% of patients there is an urgent need to identify early biomarkers of resistance to rituximab to adapt therapeutic management. In nephrotic patients, rituximab is found in the blood more transiently than in other autoimmune diseases without proteinuria, due to rituximab wasting in the urine. However, rituximab immunomonitoring is not routinely performed. We evaluated the predictive value of serum rituximab levels in patients with pMN three months after rituximab injection (month-3) on clinical remission rates six months (month-6) and 12 months (month-12) after injection and investigated predictive factors for serum rituximab levels at month-3. Sixty-eight patients treated with rituximab between July 2015 and January 2020 from two French nephrology centers were included. We identified residual rituximab levels at month-3 as a novel early predictor of remission at month-6 (p <0.0001) and month-12 (p = 0.001). Reduced likelihood of remission in patients with undetectable rituximab at month-3 was associated with lower serum albumin and higher anti-PLA2R1 titers at baseline and with lower serum albumin, higher proteinuria, higher CD19+ counts and higher anti-PLA2R1 titers during follow-up. In multivariate analysis, high baseline proteinuria and undetectable rituximab levels at month-3 were independent risk factors for treatment failure at month-6 and high baseline weight and undetectable rituximab levels at month-3 were independent risk factors for treatment failure at month-12. We identified serum albumin at baseline as a predictive factor for serum rituximab levels at month-3. Patients with serum albumin below 22.5 g/L at baseline had an 8.66-fold higher risk of having undetectable rituximab levels at month-3. Therefore, rituximab immunomonitoring in pMN patients treated with rituximab would allow the detection of patients at risk of treatment failure as early as month-3. Studies are needed to assess whether patients with low residual rituximab levels at month-3 may benefit from an early additional course of rituximab.